5,17-Dibromo-26,28-dihydroxy-25,27-dipropoxy-2,8,14,20-tetrathiacalix[4]arene - Liu, Ling-Ling (International Union of Crystallography, 2011)
In the title compound, C(30)H(26)Br(2)O(4)S(4), the thiacalix[4]arene unit adopts a pinched cone conformation, with one of the ether-substituted rings bent towards the calix cavity and the two phenolic rings bent outwards. The phenyl rings make dihedral angles of 27.12 (9), 36.71 (10), 75.04 (8), and 76.01 (7)° with the virtual plane defined by the four bridging S atoms. The two opposite ether-substituted rings are almost parallel to each other, with an interplanar anagle of 2.99 (12)°, while the two phenolic rings are nearly perpendicular to each other, making a dihedral angle of 74.52 (11)° and a Br⋯Br distance of 13.17 (2) Å. Two intramolecular O—H⋯O hydrogen bonds between the OH groups and the same ether O atom stabilize the cone conformation. In the crystal, two different chains of molecules, one with alternating and the other with tail-to-tail orientations, are formed by intermolecular offset-face-to-face π–π stacking interactions with distances of 3.606 (3) to 4.488 (4) Å between the centroids of the aromatic rings.